# CHAPTER 10 QUADRATIC EXPRESSIONS AND EQUATIONS

Important concepts: 1. A Quadratic Expression is an expression in the form of ax 2 + bx + c where a, b, and c are constants with a ≠ 0 and x is a variable. Example: 2x 2 + 4x − 5

2. A Quadratic Equation has the general form is ax 2 + bx + c = 0 . 3. In a Quadratic Equation, there are rules to be fulfilled. That is:
i. ii. The highest power of the variable is 2. Involves only one variable.

4. Finding the solutions for a quadratic equation means finding the roots of the quadratic equation. 5. Tip SPM
( a − b) 2 = ( a − b)( a − b) = a 2 − 2ab + b 2 ( a + b) 2 = ( a + b)( a + b) = a 2 + 2ab + b 2

a 2 − b 2 = ( a + b)( a − b)

10.1 Quadratic Expressions ax2 + bx +c, where a, b, c are constant, a a. Identify quadratic expressions. Example: State whether the following expressions are quadratic expressions. 1 i. m2 – 4m + is a quadratic expression. 2 ii. 5x –3 = 2x2 is not a quadratic expression. Exercise i. 2y2 + 4

≠ 0 and x is a variable.

ii.

4p2 + 2q – 3

b.

1

Example Multiply and simplify the following expressions. i. m(2m –3) = 2m2 – 3m

Exercise i. ii p( p – 3p) = (r – 3)(2r +5) =

ii. (x–2)(2x+3) =2x – x – 6

2

10.2 Expansion involving brackets 10.2.1 Expansion involving one bracket Example: Expand each of the following : 1. 2(2x + y) =
2( 2 x + y ) = 2 × 2 x + 2 × y = 4x +2 y

Exercise: i. 3( 4b + 2d ) =

ii.

1 ( 2c − 5d ) = 2

2. 3a(4a–5b) =
3a ( 4a − 5b) = 3a × 4a − 3a × 5b

i.. − 4 x( 2 y − 3 x ) =

= 12 a 2 −15 ab ii. 12 j ( 1 j − 2k ) = 3

3. − 4h(−3 + 5h + 2 g ) =

i. − 2m(−5 − 6m + 4n) =

2

− 4h( −3 + 5h + 2 g ) = −4h × −3 + ( −4h) ×5h + ( −4h) × 2 g = 12 h − 20 h 2 −8 gh

ii. 4c (3c +

2 d −12 ) = 3

1 4. 12 b(9c + b) = 3

i.

k (6k + 2) = 2

1 1 12 b(9c + b) = 12 b × 9c +12 b × b 3 3 = 108 bc + 4b 2 ii.
3 5 x (10 x − ) = 5 6

10.2.2 Expansion involving two brackets. Example: Expand each of the following: 1. ( a + b)( c + d ) =      Exercise: i. ( x + y )( w + z ) =   

( a + b)( c + d ) = a × c + a × d + b × c + b × d

= ac + ad + bc + bd i. (2a + b)( 6a + 2b) =   
3 5 ii. ( s − 2t )( 5s − t ) = 5 6

2. ( x − 2 y )( 3 x − 4 y ) =   

( x − 2 y )( 3 x − 4 y ) = x ×3 x + x × ( −4 y ) + ( −2 y ) ×3 x + ( −2 y ) × ( −4 y )

 = 3 x − 4 xy − 2 xy + 8 y = 3 x 2 − 6 xy + 8 y 2
2 2

3. (2 f + g )( f − 2 g ) =

i. (3 z + 4 y )( 5 z − y ) =

3

(2 f + g )( f − 2 g ) = 2 f × f + 2 f × ( −2 g ) + g × f + g × ( −2 g ) = 2 f 2 − 4 fg + fg − 2 g 2 = 2 f 2 − 3 fg − 2 g 2

ii. ( 2d + 5b)( d − 7b) =

10.2.3 Expand the following: 1. (a + b) 2 =
(a + b) 2 = ( a + b)( a + b)

i. (3 x + y ) 2 =

= a 2 + ab + ab + b 2 = a 2 + 2ab + b 2

ii. ( p + 2q ) 2 =

2. ( h − k ) 2 =

i. ( s − 2 z ) 2 =

(h − k ) 2 = (h − k )(h − k )
= h 2 − hk − hk + k 2 = h 2 − 2hk + k 2
1  ii.  c − 4  = 2  
2

10.3

Quadratic expressions of the form ax2 + bx + c and ax2 + bx can be factorised if we find their highest common factors (HCF) .

4

10.3.1 Factorisation of Algebraic Expression Example Factorise the following quadratic expressions 1. 3x2 + 6 = 3 ( x2 + 2) , 3 is the highest common factor 1 2 1 w − w= 2 2 Exercise i. 5x2 +10 1 2 3 m − m= 4 4

2.

i. 2

1 2 1 1 w − w = w( w −1) 2 2 2

1 1 2 ii. 1 ab + 2 b = 3 3

3.

1 2 1 k + k= 4 2

i. 4 1 2 1 2 1 k + k 4 2 1 2 k +k 2 1 k +1 2

1 2 1 j + j= 7 7

k
1 2 1 1 1 k + k = k ( k + 1) 4 2 2 2

ii. 3

1 1 p − p2 = 4 2

10.4 Quadratic Equations 10.4.1 (a) Identify quadratic equation Example Identify whether the following are Exercise

5

quadratic equations. i. 3x2 – 4x = 5 is a quadratic equation with one unknown. The highest power is 2. ii. x3 + 5 = 0 is not a quadratic equation. The highest power is 3.

i. 2y – 3y2 + 4 = 0

ii. 2p(p2 + 3)= 7

(b) Write quadratic equation in general form : ax2 + bx – c = 0
Example i. 3 – 2y = y2 y2 + 2y – 3 =0 ii. (x – 2) 2 – 4 = 0 x2 – 4x + 4 – 4 = 0 x2 – 4x = 0 10.5 Understand the concept of roots 10.5.1 Determine the roots for quadratic equations Example i. (x – 3)(x + 5) = 0 x – 3 = 0 or x + 5 =0 x = 3 or x = –5 ii. (2p – 5)(p +2) = 0 2p –5 = 0 or p+2=0
2 or p = – 2 5 k 2 −8 iii. =k 7 k2 – 8 = 7k k2 –7k – 8 = 0 (k – 8)((k + 1) = 0 k – 8 = 0 or k + 1 = 0

Exercise i. 2y + 4 = 3y2

ii. (x + 3)(2x + 1) = 3

Exercise i. (x + 4)(x –1) =0

ii. (5m – 2)(3m + 1) = 0

P=

iii.

x2 − 6 =x 5

6

k = 8 or k = –1 iv. f2 + 15 = f 8 f2 + 15 = 8f f2 – 8f + 15 =0 (f – 3)(f – 5) =0 f – 3 = 0 or f – 5 = 0 f = 3 or f = 5 v. (f –1)(f –2) –6 = 0 f2 – 2f –1f + 2 – 6 =0 f2 –3f – 4 = 0 (f – 4)( f + 1) = 0 f – 4 = 0 or f + 1 =0 f = 4 or f = –1 vi. (y – 7)2 – 52 =0 (y –7)(y – 7) – 25= 0 y2 –7y –7y + 49 –25 =0 y2 –14y +24 = 0 (y – 2)(y – 12) = 0 y = 2 or y = 12 iv.
p2 + 4 =p 5

v. (p – 3)(p – 2) – 12 =0

vi. (p – 3)2 – 25 = 0

10.6 Questions based on examination format

1.

(2 y −1)( 3 y + 4) =

A (6 y 2 + 8 y − 4) B (6 y 2 − 5 y − 4)
1  2. Expand  p −1 . 4 
2

C ( 6 y 2 + 5 y − 4) D (5 y 2 + 6 y + 4)

1 2 p − p +1 16 1 2 p − p +1 B 4 1 1 3. Factorise k 2 − k . 5 10 1  1 kk −  A 5  2 A

1 2 1 p − p +1 4 2 1 2 1 p − p +1 D 16 16 C

C

1  2 1  k − k  10  10 

7

1 k ( 2k +1) 10 1  1  1   k + k  k − k  10  2  2  B

D

4. Given f ( x) = (2 x +1) 2 − 9 . Find the roots when f ( x) = −5 .
` 1 3 and − 2 2 1 3 B − and 2 2 A C 2 and -3 D -2 and 3

5. Find the roots of ( w + 3)( w −1) − 45 = 0 .
A –6 and 8 B 6 and –8 6. The diagram shows a triangle. C –3 and 16 D 3 and –16

(x-5)

x

The area of the triangle is 7 units. The height of the triangle is A 2 units B –2 units 7. Given x2 + x = 6, find the values of x. A 6 atau –1 B –6 atau 1 8. Given (m − 2)( m − 3) −12 = 0 , find the values of m. A –1 and 6 B 1 and -6 C –2 and –3 D 2 and 3 C 2 atau –3 D –2 atau 3 C 7 units D –7 units

9. Given r 2 − 4r + 3 = 2( r −1) , find the values of r.
A –5 and -3 B 5 and 3 10. The figure shows a rectangle.

C –5 and –1 D 5 and 1

8

(K + 5) cm

K cm

Given that total area of the rectangle is 24 cm 2 . Find the length of the rectangle. A –3 cm B 3 cm 11. ( p − 3q ) 2 + 5 pq = A p 2 − pq + 9q 2 B p 2 − 8 pq − 9q 2 C –8 cm D 8 cm

C p 2 −11 pq + 9q 2 D p 2 + 5 pq + 9q 2

12. Given

x−3 4 = , the values of x are x +4 2
5 or 4 4 D. –5 or – 4 C.
1 atau 6 2

A. 5 or 4 C. –5 or 4

13. Find the values of x if (2x + 1)(x-6) =0
A.
1 atau 6 2

C. – D.

B. –1 atau 6 A b = 1, c = –12 B b = 1, c = 12

1 atau 6 2

14. . Given that a 2 + a −12 = (a + b)( a + c) . Find the value b and c.
C b = 3, c = - 4 D b = -3, c = 4

15. Factorise 10 x 2 + x − 2 .
A (10 x +1)( x − 2) B (5 x − 2)( x +1) C ( x +1)(10 x − 2) D (5 x + 2)( x −1)
2m 2 − 5 =1. 9m

16. Find the values of m such that
A − B
1 and 5 2

C −1 and 5 D 1 and −5

1 and −5 2 17. Find the values of x such that 3 x( x + 4) =15 . A –5 and 1 B 5 and –1

C –5 and –11 D 5 and 11 5 = x + 2 are x −2

18. The roots of

9

A 2 and –2 B 3 and –3

C 4 and – 4 D 5 and –5

19. Fatorise 48 f 2 −88 f + 32 .
A (6 f 2 −11 f + 4) B (6 f 2 +11 f − 4) C 8(6 f 2 −11 f + 4) D 8(6 f 2 +11 f − 4)
22 ) =1 . 5

20. Find the values of u which satisfy u (3u +
17 15 17 B -1 and − 15 A 1 and −

C

1 5 and − 5 3 1 5 D − and 5 3

10.7 Past Year SPM Questions
1. (3 p − m)( p + 2m) = A 3 p 2 + 5 pm − 2m 2 B 3 p 2 − 5 pm + 2m 2 2. (3 – 4x)(2 + x) + 3(x – 5) = A - 3x2 + 3x – 5 B - 4x2 – 2x – 9 Nov 2004 3. 3 x ( x − 2 y ) − (3 x − y ) 2 = A −6 xy + y 2 B −6x 2 − y 2 C 3 p 2 + 7 pm − 2m 2 D 3 p 2 − 7 pm + 2m 2 C - 4x2 – 3x + 1 D - 8x2 + 6x – 15

C − 6 x 2 − 6 xy + y 2 D − 3 x 2 − 9 xy − y 2

Nov 2005 4. (3h + 4)( 2h − 5) = A 6h 2 − 7 h + 20 B 6h 2 − 7 h − 20 Nov 2006 5. 3x2 - x ( 1 – x ) A 2x2 – 1

C 6h 2 − 23h + 20 D 6h 2 − 23 h − 20

C 4x2 – 1

10

B 2x2 – x Nov 2007

D 4x2 – x

6. 5pq ─ 2(1─pq) = A 3pq – 2 B 4pq - 2 Jun 2008 7. (2x – y) 2 - x(x – y) A 3x2 – 3xy + y2 B 3x2 – 5xy + y2 Nov 2008 8. (x – y)(5x + 3y) – x(x – y) A 4x2 – xy – 3y2 B 4x2 – 3xy – 3y2

C 6pq - 2 D 7pq – 2

C 3x2 + xy - y2 D 3x2 – 5xy – y2

C 4x2 – xy + 3y2 D 4x2 – 3xy + 3y2

10.1 (a) 10.3.1 i. Yes ii. no i. p 2 − 3 p 2 ii. 2r 2 − r − 15 1. i. 5( x 2 + 2) 2. i. (b)
3 m(3m −1) 4 1 ii. b(ab + 2) 3

11

10.2.1 1 i. 12b + 6d 5 ii. c − d 2 2. i. −8 xy +12 x 2 ii. 4 j 2 − 24 jk 3. i. 10 m + 12 m 2 − 8mn 8 2 ii. 12 c + cd − 48 c 3 4. i. 3k + k 1 2 ii. 6 x − x 2
2

3. i.

1 j ( 4 j +1) 7 1 1 p (3 − p ) ii. 2 2

10.4.1 a) i. Yes ii. No (b) i. 3 y 2 − 2 y − 4 = 0 ii. 2 x 2 + 7 x = 0 10.5.1 i. -4 , 1 2 1 ii. , − 5 3 iii. -1 , 6 iv. 1 , 4 v. -1 , 6 vi. 8 , -2 10.6 1C 2D 3A 4A 5B 6 C 7 C 8 A 9 D 10 B 11 A 12 C 13 C 14 A 15 A 16 B 17 A 18 D 19 C 20 C

10.2.2 1. i. xw + xz + wy + yz 2. i. 12 a 2 + 10 ab + 2b 2 1 5 2 2 ii. 3s −10 st + t 2 3 3. i. 15 z 2 +17 yz − 4 y 2 ii. 2d 2 − 9bd − 35b 2 10.2.3 1. i. 9 x 2 + 6 xy + y 2 ii. p 2 + 4 pq + 4q 2 2. i. s 2 − 4sz + 4 z 2 1 2 ii. c − 4c + 16 4

10.7 SPM Past Year Questions 1. B 2. B 3. B 4. B 4. D 6. D 7. A 8. A